Lutembacher Syndrome An Echocardiography Assesment: A Rare Case - Pangestu, Hedaya Pancar; Rizky, Kiki (The International Journal of Medical Science and Health Research, 2024)
Background: Lutembacher Syndrome (LS) is a rare heart defect, characterized by the presence of Atrial Septal Defect (ASD) (congenital or acquired) and Mitral Stenosis (MS) (congenital or acquired). Case Description: A 56 years old woman came to the cardiovascular clinic at Balaraja Hospital with complaints of shortness of breath has been felt since the last 3 months. shortness of breath has been aggravated by activity and relieved by rest. Shortness of breath is also felt when lying down, if she sleeps, she has to use 2-3 pillows or an elevated position. On physical examination there was an increase in jugular venous pressure (JVP) 5+4 cm, irregular 1st and 2nd heart sounds, and a grade 2/4 diastolic murmur at the apex and a pansystolic murmur were found. grade 3/6 in the tricuspid area. During auscultation, wide fixed splitting was also found. On examination of the extremities, edema was found in both legs. An electrocardiogram (ECG) examination revealed atrial fibrillation (AF), bigemini ventricular extrasystole (VES) and echocardiography conclusion were found Reumatic Heart Disease, MS severe, mild mitral regurgitation, severe tricuspid regurgitation, pulmonary hypertension, ASD secundum left to right shunt. Conclusion: Lutembacher Syndrome is still a rare disease, including in Indonesia. If diagnosed early and appropriate therapy is carried out, it will provide a good prognosis, if the diagnosis is late, it will increase mortality due to heart failure, arrhytmia and embolic stroke.